2010
DOI: 10.1200/jco.2009.27.1361
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing Technology Reveals a Characteristic Pattern of Molecular Mutations in 72.8% of Chronic Myelomonocytic Leukemia by Detecting Frequent Alterations in TET2, CBL, RAS, and RUNX1

Abstract: The number of molecular markers used to categorize myeloid neoplasms is constantly increasing. Here, NGS screening has been demonstrated to support a comprehensive characterization of the molecular background in CMML. A pattern of molecular mutations translates into different biologic and prognostic categories of CMML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
246
1
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(261 citation statements)
references
References 29 publications
13
246
1
1
Order By: Relevance
“…29,30 Although TET2 mutations can represent early molecular events in myeloproliferative neoplasms, in a recent study of JAK2 mutation-positive myeloproliferative neoplasms based on colony assays, genotyping for TET2 and JAK2 mutations, it was demonstrated that TET2 can be a late event in the progression of myeloproliferative neoplasms and may represent an acquired abnormality in a separate (JAK2 mutation-negative) clone. 31 It is intriguing to speculate that the acquisition of KRAS, TET2 or other mutagenic events could have played a role in the phenotypic shift observed in our cases. One could hypothesize that possibly either owing to clonal defect present at the disease onset in only a minority of the cells and its subsequent expansion, or because of a new genetic event acquired later in the course of the disease, some patients with myeloproliferative neoplasms have a monocytic proliferation capacity that eventually manifests as a chronic myelomonocytic leukemia or chronic myelomonocytic leukemia-like phenotype.…”
Section: Discussionmentioning
confidence: 84%
“…29,30 Although TET2 mutations can represent early molecular events in myeloproliferative neoplasms, in a recent study of JAK2 mutation-positive myeloproliferative neoplasms based on colony assays, genotyping for TET2 and JAK2 mutations, it was demonstrated that TET2 can be a late event in the progression of myeloproliferative neoplasms and may represent an acquired abnormality in a separate (JAK2 mutation-negative) clone. 31 It is intriguing to speculate that the acquisition of KRAS, TET2 or other mutagenic events could have played a role in the phenotypic shift observed in our cases. One could hypothesize that possibly either owing to clonal defect present at the disease onset in only a minority of the cells and its subsequent expansion, or because of a new genetic event acquired later in the course of the disease, some patients with myeloproliferative neoplasms have a monocytic proliferation capacity that eventually manifests as a chronic myelomonocytic leukemia or chronic myelomonocytic leukemia-like phenotype.…”
Section: Discussionmentioning
confidence: 84%
“…The advent of next generation sequencing technology has led to the identification of molecular aberrations in 90% of patients with CMML [9,14,26]. These can broadly be divided into four categories: mutations involving epigenetic regulator genes such as EZH2, ASXL1, TET2, DNMT3A, IDH1, and IDH2 [9,10,14,27], mutations involving the spliceosome machinery such as SF3B1, SRSF2, U2AF35, ZRSR2, SF3A1, PRPF40B, U2AF65, and SF1 [13,14,19,20], mutations involving DNA damage response genes such as Tp53 [28], and mutations involving genes regulating cellular/receptor tyrosine kinases and (13) 12 (100) 9 (75) 3 (25) delP95R-R102-7 (8) 7 (100) 3 (43) 1 (14) R94-P95insR-1 (1) 1 ( (25) 5 (100) 5 (100) 0 (0) Q157G-1 (5) 0 (0) 0 (0) 1 (100) R158H-1 (5) 1 (100) 1 (100) 0 (0) CMML-1, chronic myelomonocytic leukemia-1; SF3B1, splicing factor 3B, subunit 1; SRSF2, serine/arginine-rich splicing factor 2; U2AF35, U2 small nuclear RNA auxiliary factor 1.…”
Section: Discussionmentioning
confidence: 99%
“…research article transcription factors such as JAK2, KRAS, NRAS, and RUNX1 [26,29]. Thus far, in CMML loss of function gene mutations involving ASXL1 and EZH2 have been associated with poor outcome [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…responsible for its repression during MK differentiation, which may explain the presence of low ploidy MK in runx1 f/f(Mx1 Cre + ) mice 24,25 , as well as in hereditary or acquired haematological disorders associated with RUNX1 loss-of-function mutations 35,36 . Low-ploidy MK has been observed in KO of other transcription factors, such as GATA1 or FLI-1 (refs 37,38).…”
Section: Discussionmentioning
confidence: 99%